Sierra Leone : Request for Disbursement under the Rapid Credit Facility-Press Release; Staff Report; and Statement by the Executive Director for Sierra Leone. (IMF Staff Country Reports; Country Report ;, 2020)
This paper discusses Sierra Leone's Request for Disbursement Under the Rapid Credit Facility (RCF). The coronavirus disease 2019 (COVID-19) pandemic puts Sierra Leone's population at risk and is a serious blow to the economy, which has just started to recover. The number of COVID-19 cases is increasing rapidly, threatening the fragile health system. The drop in external demand and essential measures to contain the spread of the virus are sharply curtailing economic activity. The authorities are taking decisive actions to mitigate the health and socio-economic impact of the pandemic. In collaboration with development partners, they are scaling up urgent health spending and introducing measures, including boosting social safety nets and ensuring access to credit for affected businesses. The shock has generated a large balance of payments need. Emergency financing under the RCF will help meet this financing gap and create room for pandemic-related spending. With significant downside risks and a tight financing situation threatening to reverse Sierra Leone's progress toward the Sustainable Development Goals, additional grant support from the international community is urgently needed.